Kajian Yuridis Undang ¬- Undang Nomor 2 Tahun 2012 tentang Pengadaan Tanah bagi Pembangunan untuk Kepentingan Umum dalam Putusan Mk.50/Puu-X/2012 - Berliani, Annisa; Sutrisno, Hafiz; Heriyanti, Yuli (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2023)
This study aims to find out how the legal protection of citizens' constitutional rights against land expropriation for the public interest by the state. The formulation of the problem proposed is first, why the applicant filed a review of Law no. 2 of 2012 concerning land acquisition for development in the public interest to the Constitutional Court and second, the basis for consideration of the constitutional judges in the Constitutional Court's decision no. 50/PUU-X/2012 which rejected the applicant's application. Using the research method of juridical normative analysis, with this approach we can describe and describe how the legal protection of citizens' constitutional rights against land expropriation for the public interest by the state. The research data was collected by means of a literature study using a conceptual approach. The results of the study concluded that first, Law no. 2 of 2012 is considered to ignore the interests of the community for the sake of business interests by certain groups so that the state is considered to have legalized the seizure of people's land which will cause the lower class people to suffer and secondly, the applicant's arguments have no legal basis. According to the Constitutional Court Judge, although the state provides opportunities for the private sector to be able to participate in fulfilling the public interest, the state can still determine policies related to the public interest, for example in setting toll rates managed by the private sector, so that the private sector cannot fully determine road tariffs by themselves. the toll road that is the investment of the person concerned. This study recommends the need for improvements and reforms in drafting the law should consider more input from the community, especially those who will be affected by the regulation, so that there are no lawsuits from the community.